Uji Efektivitas Ekstrak Daun Renggak (Amomum dealbatum Roxb.) Sebagai Antihiperurisemia Pada Mencit - Sovia, Fitriwati; Al-Adawiyah , Rosita; Yuliana , Tri Puspita (Journal of Pharmaceutical and Sciences, 2025)
Background: Hyperuricemia, resulting from excessive uric acid levels, can trigger chronic inflammation and increase the risk of gout. Conventional therapies such as allopurinol are associated with adverse effects, highlighting the need for natural alternatives. Renggak leaves (Amomum dealbatum Roxb.), an endemic plant from Lombok rich in flavonoids, have potential as xanthine oxidase inhibitors but remain underexplored. Objective: To evaluate the antihyperuricemic effect of renggak leaf extract in male white mice, determine the optimal dosage, and compare its efficacy with allopurinol. Methods: This study employed a pretest-posttest control group design. Hyperuricemia was induced using chicken liver juice administered for 14 days. The animals were divided into five groups: negative control (1% CMC-Na), positive control (allopurinol 10 mg/kg BW), and three extract-treated groups (50, 250, and 500 mg/kg BW), which received the extract for 21 days. Results: All extract doses significantly reduced uric acid levels (P < 0.05). The 500 mg/kg BW dose was the most effective (44.54% reduction), showing no significant difference compared to allopurinol (48.52%; p = 0.490). The effect is presumed to occur through xanthine oxidase inhibition by flavonoids. Conclusion: Renggak leaf extract, particularly at a dose of 500 mg/kgBW, shows potential as an alternative therapy for hyperuricemia with efficacy comparable to allopurinol. However, further studies such as toxicity tests, pharmacokinetic evaluations, and clinical trials are needed to validate its broader application.